Inhibitory test of binahong (Anredera cordifolia (Ten.) steenis) n-hexane fraction against bacillus subtillis bacteria by diffusion method - Fitri Kurniasari; Puput Dwi Lestari (Surya Hijau Manfaat, 2023)
Binahong plants (Anredera cordifolia (Ten.) Steenis) contain alkaloids,flavonoids,saponins, and terpenoids, the chemical compounds of binahong leaves have many antibacterial properties. This study aims to determine the antibacterial inhibition of n-hexane (Anredera cofdifolia Ten.) Steenis) against Bacillus Subtillis. This type of research is experimental descriptive, binahong leaf n-hexane fraction was previously obtained by extraction using maceration method with 70% ethanol solvent obtained by using a 10% DMSO dissolved and tested for antibacterial inhibition with the method of solid well diffusion against Bacillus Subtillis in the series of concentrations of 20%,40%,60% dan 80% positive controls used were chloramphenicol 10% and negative control DMSO 20%. The results of the study showed that n-hexane fraction of binahong leaves (Anreders cordifolia (Ten.) Steenis) was able to inhibit the growth of the bacterium Bacillus subtillis. The greater the concentration used, the greater the results obtained.